The Legal Consequences and The Psychological Divorce Impact Against Women in Padang City - Bakhtiar Bakhtiar; Rahmadianti Aulia (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2022)
This research is motivated by the rise of divorce cases in the Padang City Religious Court. When the divorce case is decided by the Religious Courts, there will be legal consequences from the decision of course this decision has an impact on individual psychology, and interestingly the psychological impact is more common among women. This study aims to find out the factors behind the occurrence of lawsuits in the Padang Religious Court and to identify and reveal the psychological impact caused by divorce lawsuits on women in the Padang Religious Courts. The research was conducted using qualitative methods with interview and observation techniques. The results showed that the factors behind the occurrence of divorce were jealousy, cheating, domestic violence (domestic violence), dishonesty and unclear finances, unmeeting economic needs, drug users and dealers, disobedience, and harassing religion. The legal consequences caused by a lawsuit at the Padang Religious Court are not being allowed to reconcile during the iddah period, paying court fees, dividing assets, and the rights of the child's guardian. While the psychological impact of divorce on women is that subjects R, YM, and S did not see any post-divorce psychological disorders, while in NT, they felt traumatized by their marriage and NL showed feelings of shame and inadequacy with their new status